AGRO-MORPHOLOGICAL CHARACTERIZATION AND GENETIC DIVERSITY OF ð˜—ð˜¢ð˜¶ð˜ð˜ð˜ªð˜¯ð˜ªð˜¢ ð˜¤ð˜¶ð˜±ð˜¢ð˜¯ð˜¢ var. ð˜´ð˜°ð˜³ð˜£ð˜ªð˜ð˜ªð˜´ - Ozorio, Pablo Roberto da Silva; Atroch, AndrÃ© Luiz; Nascimento Filho, Firmino JosÃ© do (REVISTA DE AGRICULTURA, 2019)
Based on agro-morphological traits, this study aimed to describe and quantify the genetic diversity between eighteen guarana cultivars from the guarana breeding program, to identify cultivars for use in multiple-purpose in breeding programs to obtain segregating populations with great variability and diversity. Dis-similarity between cultivars was calculated using Gowerâ€™s algorithm and a dendrogram was obtained using the UPGMA algorithm. High genetic variability and diversity was identified between guarana cultivars via 20 morpho-agronomic traits. Two groups and six subgroups of genetic diversity were identified. Crosses between clones of different subgroups may produce high variability and diversity in segregating populations, increasing the capacity to select for superior genotypes in these populations.